Impact of financial flexibility on debt maturity, investment decisions and performance of firms in Malaysia and Australia - Ng, Huey Chyi (2018)
Financial flexibility was defined as a firm’s ability to respond in a timely manner to unanticipated shocks or changes in firms’ cash flows and investment opportunity. Financially flexible firm reserves some borrowing power to avoid any financial distress, which enable firm to issue new debts or adjusting capital structure at low cost. Firm’s financial flexibility, debt maturity structure and investment opportunities have been linked together with strong potential interactions. During financial crisis, firms that had over borrowed or have optimum debt-equity choice have been subjected to mismatched asset liability. Those saddled with more short term debts are facing higher default risk and interest rate risk during such times. Subsequently, many firms have had to stop operations and slash employments; some opted for liquidation. Thus, firm sustainability is also highly reliant on their financial flexibility and debt maturity structure. Research of firm’s financial flexibility is lacking despite financial flexibility being able to reduce company risk and respond effectively to any investment opportunity or financial constraint. There are also lack of research on the impact of firm’s financial flexibility on debt maturity structure, investment decisions and firm’s performance. The objectives of this thesis including determination of factors affecting firm’s capital structure and to identify the firm’s financial flexibility status; examine the relationship between firm’s financial flexibility and the firm’s debt maturity structure; study the impact of firm’s financial flexibility and debt maturity structure on their investment decision; and lastly examine the impact of firm’s financial flexibility towards firm’s performance and value. This paper study on listed companies in Malaysia and Australia due to their location in Asia Pacific region with different economy development structure and status. Study period starting from year 2000 to year 2014, yielding 10,633 observations. Panel regression has been employed for all hypotheses. The preliminary result of this study to meet the first research objective has suggested that Malaysian firms follow the pecking order theory, whereas Australian firms follow the trade-off theory. Firm’s financial flexibility has been identified by comparing targeted debt ratio and actual debt ratio. In meeting the second research objective, financially flexible firms found to have less long term debts in both Malaysia and Australia. This financially flexible firm has lower default risk and debts roll over risk due to the ability to restructure their financial policy during uncertainty or shock. Thus, they prefer short term debts rather than long term debts. Subsequently, for research objective three, mixed results being found where financial flexibility has shown no impact on firm’s investment decision in Malaysia, but Australian firms are positively impacted. Debt maturity shows positive significant impact on firm’s investment in both countries. In additional study, financial flexibility has shown negative impact on low investment firms in Malaysia, indicates that firms forgo investment opportunity to maintain financial flexibility. In Australia, financial flexibility shows strong positive impact towards the high investment activities firms only, signaling the importance of financial flexibility in high investment firms. For the last research objective, no significant result found in both countries on the impact of financial flexibility towards performance. Details investigation shows negative impact on firm’s performance in low profitability and smaller firms, whereas positive impact on high profitability and large firms. The financial flexibility helps in restructuring firm’s financial position at a lower cost, proving the important role financial flexibility plays in increasing firm’s performance and value in both countries. This study has substantiated the importance of financial flexibility and debt maturity structure in a firm’s capital structure, investment decisions and performance. The research findings provide an overviews of financial flexibility and serve as a good guide for firm’s managers, regulators as well as investors. It was recommended study on the opportunity cost of maintaining financial flexibility and adding more countries for future study.